2016
DOI: 10.12968/ijpn.2016.22.9.430
|View full text |Cite
|
Sign up to set email alerts
|

Improving end-of-life care through quality improvement

Abstract: Although end of life (EoL) care has been identified as an area for quality improvement in hospitals, the quality of care Canadian patients receive at the end of life is not well-evidenced. National statistics indicate that Canadians would prefer to die at home, yet more than 50% die in acute care hospital settings. Busy and often highly specialised acute care units may be perceived as a distressing place of death for both patients and their families. Furthermore, many clinicians are not trained in diagnosing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…Today, special interest is growing in experiential learning because constant exposure to the process of dying helps nurses learn about the care of terminal patients (15) . Insufficient nursing knowledge of research (16) was improved by educational projects and evidence-based practice guides for the care of dying patients and their families (17) . Barriers such as gaps in the knowledge of research and the feeling of a lack of support and leadership on the part of nurses make it difficult to implement evidence-based care in practice (18) .…”
Section: Introductionmentioning
confidence: 99%
“…Today, special interest is growing in experiential learning because constant exposure to the process of dying helps nurses learn about the care of terminal patients (15) . Insufficient nursing knowledge of research (16) was improved by educational projects and evidence-based practice guides for the care of dying patients and their families (17) . Barriers such as gaps in the knowledge of research and the feeling of a lack of support and leadership on the part of nurses make it difficult to implement evidence-based care in practice (18) .…”
Section: Introductionmentioning
confidence: 99%
“…In-services were conducted on the hospital's general internal medicine and oncology units, as a previous study demonstrated that these units generate the highest volume of referrals for end-of-life care. [ 18 ] Nurses were asked to complete a baseline survey and a follow-up survey after the in-service training.…”
Section: Methodsmentioning
confidence: 99%
“…Our hospital developed and implemented a standardized approach to EOL care, the CMOS, as previously described. 21 The CMOS was created through a rigorous approach, the rationale of which was to facilitate hospital-wide education for identifying, evaluating, and addressing palliative needs of "imminently dying patients" with or without a malignancy. Standardized order sets can be an invaluable tool in establishing best practices for EOL care in acute care settings.…”
Section: Comfort Measures Order Set With Cied Deactivation Embeddedmentioning
confidence: 99%
“…22,23 The CMOS contains elements of symptom assessment and management, patient/family education, and guidance on offering spiritual and emotional support. 21 The deactivation of ICDs is embedded in the CMOS order set. Order sets decrease variability of orders among prescribing clinicians who are less familiar with managing EOL care symptoms while encouraging all clinicians to address important facets of patients' needs in the final hours to days of life.…”
Section: Comfort Measures Order Set With Cied Deactivation Embeddedmentioning
confidence: 99%